Probability Scale of Vessel Risks on a Shipping Company - Shahro Muttaqin; Christiono Utomo (Institut Teknologi Sepuluh Nopember, 2020)
Indonesia as one of the biggest maritime country in the world, makes sea transportation an important mode of transportation in Indonesia. A sea transportation is a vessel owned by a shipowner or shipping company. The owners have responsibilities in the operation of vessels and its cargos. Shipowners barely understand the risks that follow them on the sailing such as PT X. This private company is one of shipping companies that has sailing route from Surabaya to west Indonesia. High level of vessel accidents in west Indonesia makes the Java Sea a risk-prone area by NTSC. This paper reports interview with PT X and validated by a marine expert to analyze risk factors in vessels. The method conducted was a survey to collect mean index data for probability risk analysis. It is identified that the highest probability of risk is caused by the lack of experiences from the crews, work accidents on the boat, high fuel cost and others. Hence, this report concludes that this examination of risk probability of ship events to a ship company shows types of risk that have the highest probability in order to be mitigated so that the loss will be able to be reduced